An Overview of the use of Electronic Medical Records in Outpatient Services at JIH Purwokerto Hospital - Farizka Hannesty; Dion Romodon (UM Purwokerto Press, 2026)
Electronic Medical Records (EMRs), which utilize digital technology, have been implemented in several hospitals in Indonesia and offer advantages such as easier retrieval of patient data and medical history, improved time efficiency, greater effectiveness, and enhanced data security. This study aimed to describe the use of EMRs in outpatient services at JIH Purwokerto Hospital. The research employed a descriptive qualitative design using interview methods to collect data. The findings indicated that, in terms of task implementation, staff performance was considered good and effective in supporting the application of EMRs in outpatient services. From the program planning perspective, the EMR system had been successfully implemented and continuously developed with updated features. Regarding regulations and programs, the hospital had established Standard Operating Procedures (SOPs) for electronic medical records as well as policies to ensure the confidentiality of medical record data. In terms of benefits, ideal conditions, and obstacles, the implementation of EMRs provided significant advantages for users; however, the ideal implementation had not been fully achieved due to several existing challenges.